Ukrainian “The Mandate” by N. Erdman (based on periodicals of 1925–1926) - Борбунюк, Валентина Олексіївна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2019)
In a study on the material of Ukrainian, in particular, Kharkiv, periodicals, an attempt was made to reconstruct the play by N. Erdman “The Mandate”. This is one of the most popular stagings in the national theater repertoire of the 1925/1926 season. The scientific novelty of the work is due to the fact that the problems of reception and interpretation of “The Mandate” play by the Ukrainian theater critics of the 1920s have not yet become the subject of a special scientific study. The research methodology consists of applying an integrated approach, in particular, using historical, cultural, typological, and intertextual methods for the analysis. This approach allowed us to get an idea of such components of the staging as the director’s, actors’ activities, and the audience’s reaction. In addition, an attempt was made to classify domestic theater criticism of the 1920s. It is shown that the director’s theater influenced the writers. However, despite the commitment of critics to a particular aesthetic system, the sociological trend dominated in their comments, which often led to simplified perception and interpretation. It has been established that the emergence of the Ukrainian stage history of “The Mandate” is primarily due to the repertoire crisis of domestic theaters, the lack of plays, with the exception of M. Kulish’s works, that would reflect contemporary life, reproduced the Soviet life on a scene. Filling the repertoire lacunae with plays that were successful on the stages of the capital’s theaters, the newly formed groups, in particular, the Chervonozavodskyi Theater in Kharkiv, tried to acknowledge their professionalism. The principles and limits of the director’s “interference” in the art world of the play did not always correspond to the plan of the playwright and were due to the desire to establish a link between art and life. In general, the theatrical season of 1925/1926, in terms of saturation with theatrical premieres, affirmed the beginning of a new era in the Ukrainian theater and, as a result, in the Ukrainian theater criticism.